ANALISIS USAHA TANI PADI STUDI KASUS DI KELURAHAN KEROBOKAN KELOD - Nugraha, I Made Aricahya; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The production process will run if the production factors are met. The production factor consists of components including land, capital, labor, technology and management. The research objectives were (1) to analyze land area, land status, capital, labor and technology jointly influence the production of rice farmers in Kerobokan Kelod Village. (2) Analyzing land area, land status, capital and labor partially have a positive effect on the production of rice farmers in Kelod Kerobokan Kelod. (3) Analyzing the role of technology in moderating the effect of labor on rice farmer production in Kelod Kerobokan Kelod. This study uses primary data with observation methods, in-depth interviews and structured interviews, and uses moderation regression analysis techniques. The results of this study indicate that (1) land area, land status, capital, labor and technology simultaneously have a significant positive effect on the production of rice farmers in Kerobokan Kelod. (2) Area of ??land, land status, capital and labor partially have a significant positive effect on rice farmer production in Kelod Kerobokan Kelod. (3) Technology is a moderating variable that strengthens the influence of labor on the production of rice farmers in Kelod Kerobokan Kelod.   Keywords: Land Size, Land Status, Capital, Labor, Technology.